Collection of Bilateral Cleft Lip and Palate Standard Set Variables: Establishing a Baseline. Issue 8 (August 2018) - Citron, Isabelle; Ganske, Ingrid; Massenburg, Benjamin B.; Doyle, Michael; Meara, John G.; Rogers-Vizena, Carolyn R.
Abstract : Background: The International Consortium for Healthcare Outcomes Measurement recently published a consensus Standard Set of clinical and patient-centered metrics to measure outcomes for patients with cleft lip and/or palate (CLP). This study aims to evaluate how the Standard Set compares to existing data collected to anticipate the impact that the Standard Set may have on quality and quantity of outcome data. Methods: Extraction of the Standard Set data points was attempted retrospectively for all nonsyndromic patients with bilateral cleft lip and/or palate who underwent primary lip and/or palate repair by a single surgeon (JGM) between June 2007 and June 2014. Results: Bilateral cleft lip repair was performed on 32 patients of which 29 also underwent palate repair. All but one of the baseline demographic and phenotypic variables were available. All perioperative variables were collected, but data quality was heterogeneous. There were no early complications. At 5 years, 29.6% of patients were lost to follow-up; however, a degree of data was available on 11 of the 12 clinical metrics for those remaining. Of patients with Veau IV cleft palate and follow-up at age 5, 1 patient (6.7%) had an oronasal fistula and 1 had velopharyngeal incompetence requiring Furlow palatoplasty (6.7%). No patient-reported data were collected for any time point. Conclusion: Prospective collection of the International Consortium for Healthcare Outcomes Measurement Standard Set will improve consistency of clinical data and add the patient perspective currently lacking in outcome measures collected for patients with bilateral cleft.